2019
DOI: 10.2147/ott.s199601
|View full text |Cite
|
Sign up to set email alerts
|

<p>Curcumin reverses oxaliplatin resistance in human colorectal cancer via regulation of TGF-β/Smad2/3 signaling pathway</p>

Abstract: Background: Oxaliplatin (OXA) resistance is a main obstacle to the chemotherapy of colorectal cancer (CRC). Epithelial-mesenchymal transition (EMT), which is mainly regulated by TGF-β/Smad signaling pathway, has gradually been recognized as an important mechanism for tumor chemoresistance. Studies have shown that curcumin regulated EMT processes in many human cancers. However, whether curcumin could regulate OXA resistance in CRC through modulating TGF-β/Smad signaling-mediated EMT remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 41 publications
(33 reference statements)
1
31
0
Order By: Relevance
“…21 This phenomenon was observed in adriamycin-resistant breast cancer, cisplatinresistant ovarian cancer cell lines/pancreatic cancer cell lines, and OXA-resistant CRC cell lines/colorectal cancer cells. [22][23][24][25] Atsushi Okamoto et al revealed that NUSAP1 in oral squamous cell carcinoma enhanced the antitumor effect of paclitaxel. 9 Consistent with this report, we also found that NUSAP1 downregulation enhanced the chemosensitivity of BLCA cells to GEM.…”
Section: Discussionmentioning
confidence: 99%
“…21 This phenomenon was observed in adriamycin-resistant breast cancer, cisplatinresistant ovarian cancer cell lines/pancreatic cancer cell lines, and OXA-resistant CRC cell lines/colorectal cancer cells. [22][23][24][25] Atsushi Okamoto et al revealed that NUSAP1 in oral squamous cell carcinoma enhanced the antitumor effect of paclitaxel. 9 Consistent with this report, we also found that NUSAP1 downregulation enhanced the chemosensitivity of BLCA cells to GEM.…”
Section: Discussionmentioning
confidence: 99%
“…8) Clinical researches have shown that curcumin could inhibit the development of colon cancer, [9][10][11] and its combination with oxaliplatin can enhance the killing effects on various cancer cells, including colon cancer. [12][13][14] Recently, following the numerous studies and evidences on the health benefits of curcumin, the neuroprotective effects of curcumin is gaining increasing importance. [15][16][17] Therefore, the effects on both antitumor and reducing side effects of chemotherapy, curcumin will gain broad prospects of clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies clari ed that curcumin had the property of reversing chemotherapy drug resistance of tumors [32]. For example, in CRC, curcumin reversed oxaliplatin resistance via regulating the process of epithelial-mesenchymal transition [33]. What's more, Liu et al [34] reported that the regulatory effect of curcumin on LncRNAs in CRC.…”
Section: Discussionmentioning
confidence: 99%